Evaluation of the roles of HIV co-infection and socio-demographic factors as determinants of Quality of Life among Nigerians with Tuberculosis (Bangladesh Journal of Medical Science, 2018)
Background: Tuberculosis [TB] remains a major global public health problem, and particularly in resource-restricted settings with disproportionately high burden. This study is aimed at assessing quality of life [QoL] and the roles of HIV co-infection along with socio-demographic factors on QoL among subjects with TB.Methodology: This is a multi-center cross-sectional study among 440 participants recruited by multi-stage sampling technique across 40 Directly Observed Treatment Short-course [DOTS] centres. Interviews were done using designed questionnaire to collect information on socio-demographic and clinical details of respondents. Subsequently, the World Health Organization Quality of Life-BREF [WHOQOL-BREF] questionnaire was used to evaluate QoL.Results: Most (61.1%) of the participants was aged between 21 and 40 years, 61.6% were married and 74.5% had a paid job. Majority of the subjects reported fair QoL across all domains. Employment status and monthly income were significantly associated with participants overall QoL and their satisfaction with health (p